Design and Development of an E-Commerce System for Laundry Equipment and Supplies at CV Solusi Laundry - Afreza, Ahmad Nauval; Sharyanto, Sharyanto; Whendasmoro, Raditya Galih (Yayasan Bina Internusa Mabarindo, 2025)
CV Solusi Laundry is a company engaged in the supply of laundry equipment and supplies. The company’s sales process is still conducted conventionally through direct communication and social media, which limits market reach and efficiency. This study aims to design and develop a web-based e-commerce system to expand marketing reach, improve transaction efficiency, and simplify the purchasing process for customers. The research methods include observation, interviews, literature studies, and system development using the Waterfall model and Unified Modeling Language (UML). The results show that the developed e-commerce system can manage product, order, and transaction data in an integrated manner. The implementation of this system increases sales effectiveness, accelerates transactions, and improves service accessibility for customers.